2023
DOI: 10.3390/met13091599
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aluminum Content on the Microstructure, Mechanical Properties, and Hot Deformation Behavior of Mg-Al-Zn Alloys

Marie Moses,
Madlen Ullmann,
Ulrich Prahl

Abstract: This study compares AZ91 with AZ31 to investigate the influence of a higher Al content on the resulting microstructure, mechanical properties, and hot deformation behavior. While AZ31 exhibits a globular structure after casting, AZ91 shows a fully developed dendritic structure due to the promotion of dendrites. A heat treatment helped to homogenize AZ31, dissolved a large part of the Mg-Al precipitations in AZ91, and formed globular grains in AZ91. Due to the impact of Al on constitutional supercooling, AZ91 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The calculated activation energies are 140 kJ/mol (AZ31 DC) and 146 kJ/mol (AZ31 TRC) [42]. Both calculated activation energies are in a common range for the AZ31 alloys during hot deformation [49,50].…”
Section: Compression Testsmentioning
confidence: 84%
See 2 more Smart Citations
“…The calculated activation energies are 140 kJ/mol (AZ31 DC) and 146 kJ/mol (AZ31 TRC) [42]. Both calculated activation energies are in a common range for the AZ31 alloys during hot deformation [49,50].…”
Section: Compression Testsmentioning
confidence: 84%
“…As the values for AZ31 DC and AZ31 TRC correspond to 7.965 resp. 5.520, it is concluded that the dislocation climb creep is a dominant mechanism present in both alloys [42].…”
Section: Compression Testsmentioning
confidence: 90%
See 1 more Smart Citation